2005
DOI: 10.1061/(asce)1090-0241(2005)131:5(575)
|View full text |Cite
|
Sign up to set email alerts
|

Drained Shear Strength Parameters for Analysis of Landslides

Abstract: This paper presents recommendations for selecting the type and magnitude of drained shear strength parameters for analysis of landslides. In particular, the importance, existence, and use of the cohesion shear strength parameter is reviewed. For slope stability analyses, it is recommended that the shear strength be modeled using a stress dependent failure envelope or a friction angle that corresponds to the average effective normal stress acting on the slip surface passing through that particular material inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(122 citation statements)
references
References 20 publications
4
117
0
1
Order By: Relevance
“…Fig. 4͑a͒ also shows the estimated nonlinear strength envelope based on a correlation relationship between soil plasticity, overburden pressure, and residual friction angle by Stark et al ͑2005͒. A range of strengths from the correlation relationship is shown with shading because of the variable plasticity of the bedrock materials.…”
Section: Shear Strengthmentioning
confidence: 99%
“…Fig. 4͑a͒ also shows the estimated nonlinear strength envelope based on a correlation relationship between soil plasticity, overburden pressure, and residual friction angle by Stark et al ͑2005͒. A range of strengths from the correlation relationship is shown with shading because of the variable plasticity of the bedrock materials.…”
Section: Shear Strengthmentioning
confidence: 99%
“…The consolidation undrained (CU) ring shear test was then conducted on each specimen under different normal stresses. An effective normal stresses of 100 kPa or less correspond to shallow landslides or shallow portions of a slip surface (\5 m) (Stark et al 2005). In this study, experiments were conducted under a normal stress of 100, 200, and 400 kPa, respectively, corresponding to the deepseated landslide situation.…”
Section: Ring Shear Testmentioning
confidence: 99%
“…A healing mechanism of the rupture surface may also help understand its high shear strength. Stark et al (2005) presented ring shear test results on two soil specimens with a period of 230 days and suggested that a failure surface which has achieved a drained residual strength condition may undergo ''healing'' and exhibit a higher strength than the earlier residual value. Carrubba and Del Fabbro (2008) also suggested that the strength along a pre-existing shear surface may increase with time if the sliding mass stops moving and remains stable.…”
Section: Strength Along a Pre-existing Shear Surfacementioning
confidence: 99%
“…Other recommendation for stability analysis includes using effective stress cohesion of zero for residual and fully softened strength situations. [8] Hsin-Fu et al, (2006) focused for calculating the safety factor for an unsaturated slope distress from rainfall infiltration. The relationship between effective degree of saturation and safety factor indicated linear decrease, and therefore the shear strength gets reduced caused due to water content increase.…”
Section: Literature Reviewmentioning
confidence: 99%